MAXIMUM BACKPACK WEIGHT RECOMMENDED FOR CHILDREN IN SCHOOL CONTEXT: A SCOPING REVIEW - Maria João Matos; Catarina Barreiras; Constança Festas (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objectives: to map the evidence in relation to the maximum backpack weight recommended for children in school context. Methodology: suggested by the Joanna Briggs Institute. The relevance analysis of the articles, the extraction and synthesis of the data was carried out by two independent reviewers. Starting question: what is the maximum backpack weight recommended for children, from 6 to 12 years old, in school context Data sources: primary studies published in scientific databases, international guidelines and gray literature. Summary of the data: 353 publications were identified, of which 28 were included. The recommended weight percentage is divided into two categories: with recommendation (ranging from 5% -20%) and without recommendation. Conclusions: This scoping review allowed to map the evidence in relation to the maximum weight of the backpack recommended for children in school, where the value of 10% was the one that obtained the greatest consensus.